Biorremediation of heavy metals by a brewer’s yeast - Machado, Manuela D. (2006)
In this work, the suitability of live and inactivated cells of a brewing yeast strain of Saccharomyces cerevisiae NCYC1364 in the removal of Cu2+, Ni2+ and Zn2+ from solution was compared. Kinetics studies showed that 30 minutes of the contact of live or dead cells with all the metals were enough to occur the maximum removal, except for live cells with Cu2+, where the equilibrium was attained after 60 minutes. Dead cells showed a removal of 60% of Zn2+ and 30% of Ni2+, while live cells showed a removal of 22 and 17%, respectively. In the case of Cu2+, live and dead cells showed a similar removal (50%). Since dead biomass showed higher heavy metals removal, they are more appropriate to be used in further works of bioremediation.